Estrutura da oferta de arroz no município de Santarém e no Estado do Pará - Brandt, Sérgio Alberto; Martins Rezende , Alberto; Aad Neto , Alexandre; Ribon, Miguel; da Paz Puga Rebello, Armando (Revista Ceres, 2025)
The objectives of this study were to specify and evaluate the effects of selected variables on the production of rice in the município of Santarém and in eight other areas of Pará utilizing time series data estimate supply.